Bio‐Inspired Synthesis of Hollow Mesoporous Bioactive Glass Nanoparticles Using Calcium Carbonate as Solid Template. Issue 12 (28th March 2022) - Dey, Namit; Santhiya, Deenan; Das, Asmita
Abstract: We report a surfactant free route to synthesize hollow mesoporous bioactive glass nanoparticles at ambient atmospheric condition. The synthesized particles contain hollow core as a result of mild acid mediated removal of calcium carbonate nanoparticles used as hard template. Removal of template was confirmed through FTIR and XRD while round morphology and sizes below 100 nm could be observed by TEM. In addition, N2 adsorption and desorption analysis confirmed hollow and mesoporous nature of the bioactive glass shell. Interestingly, post removal of template, particles reported higher surface area, pore volume and pore diameter along with decrease in surface charge. Deposition of hydroxyapatite on hollow bioactive glass in Simulated Buffer Fluid (SBF) could be observed from Day 7 of immersion while well‐developed hydroxyapatite depositions could be observed by Day 30. This proved bioactivity of the material while cytotoxicity analysis on Human Osteosarcoma cell line (U2OS) through MTT assay proved the biocompatible nature of the hollow bioactive glass particle. Abstract : Bio‐inspired route for synthesis of bioactive glass nanoparticles is an inexpensive and environment friendly method. We report hollow mesoporous bioactive glass nanoparticles prepared through this route without surfactants as co‐template or calcination. Solid CaCO3 nanoparticles prepared using gelatin lead to assembly of mesoporous bioactive glass shell in presence of near neutral buffer. On mild acid treatment, the solid core can be etched out.